ASSESSMENT OF INTAKE AND NUTRITIONAL STATUS OF VITAMIN B1, B2, AND B6 IN MEN AND WOMEN WITH DIFFERENT PHYSICAL ACTIVITY LEVELS - Marzena Malara; Elżbieta Hübner-Woźniak; Iwona Lewandowska (Termedia Publishing House, 2013)
The purpose of the present study was to examine the nutritional status of vitamin B1, B2, and B6 in respect to dietary intake of these vitamins and activity coefficients of the erythrocyte enzymes transketolase, glutathione reductase, and aspartic aminotransferase in young men and women with different physical activity levels. The participants of this study were 20 women and 20 men with high physical activity (groups HAW and HAM, respectively), and 20 women and 20 men with low physical activity (groups LAW and LAM, respectively). The intake of vitamins B1, B2, B6, proteins, and calorie content of the diet was based on the average of the 4-day dietary recalls. To assess nutritional status of vitamin B1, B2, and B6, the activity coefficients (α) of erythrocyte transketolase (ETK), erythrocyte glutathione reductase (EGR), and erythrocyte aspartic aminotransferase (EAST) were estimated in blood hemolysates. The intake of the studied vitamins in the diet was statistically significantly lower in the female groups compared with the respective male groups. Deficiency of vitamin B6 in the diet was present more often in women than in men (in terms of the recommended dietary allowances [RDA]). Values of the activity coefficient αETK indicated that none of the groups in this study suffered the risk of vitamin B1 deficiency. The value of the activity coefficient αEGR indicated that the groups of women and men with low physical activity were more prone to vitamin B2 deficiency compared with the high physical activity groups. The risk of vitamin B6 deficiency (αEAST) in both male groups was higher than in both female groups. The obtained results do not allow for unequivocal determination of the impact of sex and the level of physical activity on intake and nutritional status of vitamin B1, B2, and B6. Independently of sex and the level of physical activity, the women and men consumed insufficient quantities of vitamins B1 and B6, although this was not always related to increased values of corresponding activity coefficients.